2017
DOI: 10.1161/hypertensionaha.117.09475
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Visit-to-Visit Blood Pressure Variability Among Individuals With Primary Proteinuric Glomerulopathies

Abstract: Hypertension and blood pressure variability (standard deviation and average real variability) in primary proteinuric glomerulopathies are not well described. Data were from 433 participants in the Nephrotic Syndrome Study Network (NEPTUNE). Hypertensive blood pressure status was defined as prior history of hypertension or blood pressure ≥140/90 mmHg for adults/≥95th% for children at baseline. Blood pressure variability was measured in participants with ≥3 visits in the first year. 296 adults (43 [IQR 32,57.8] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Greater systolic and diastolic standard deviation (SD) and average real variability were associated with greater hazard of reaching the composite end point in adults (all P < 0.01). In children, greater BPV was an independent predictor of composite endpoint (determined by systolic SD and average real variability) and complete remission (determined by systolic and diastolic average real variability); all P < 0.05 (16).…”
Section: Ambulatory Hypertension Abnormalities In Bp Circadian Rhythmentioning
confidence: 90%
See 1 more Smart Citation
“…Greater systolic and diastolic standard deviation (SD) and average real variability were associated with greater hazard of reaching the composite end point in adults (all P < 0.01). In children, greater BPV was an independent predictor of composite endpoint (determined by systolic SD and average real variability) and complete remission (determined by systolic and diastolic average real variability); all P < 0.05 (16).…”
Section: Ambulatory Hypertension Abnormalities In Bp Circadian Rhythmentioning
confidence: 90%
“…A recent review of 147 children enrolled in the Nephrotic Syndrome Study Network (NEPTUNE), consisting of 69 (46.9%) children with Minimal Change Disease (MCD), 49 (33.3%) with FSGS, 8 (5.4%) with IgA, 2 (0.04%) with Membranous Nephropathy, and 19 (12.9%) other glomerulopathy, showed that 69 (46.9%) had prior history of HTN or blood pressure ≥95th% at baseline visit. Authors reported no statistical difference in prevalence of hypertensive status between MCD (41%), FSGS (46.9%), and IgA (62.5%) subjects (16). This is possibly related to the preservation of kidney disease in the childhood years, lessening the effect of lower GFR usually seen with advancing age in FSGS patients.…”
Section: Epidemiologymentioning
confidence: 95%
“…The results reported by Sethna et al showed that the application of the association of BPV with renal outcomes could be extended to patients with primary glomerulopathy. Moreover, they further described a 5% increase in the occurrence of the composite endpoint (ESRD or eGFR decline < 40%) with a one-unit increase in the SD of SBP [22]. Aggressively lowering systolic blood pressure which lowers diastolic pressure to less than 70 mmHg may increase mortality risk for patients with chronic kidney disease according to an observational study [23].…”
Section: Discussionmentioning
confidence: 99%
“…37 The same study, when evaluating the adults with glomerulopathies, found that those with HT were at higher risk of developing end-stage renal disease in addition to a decrease of 40% or more in their estimated glomerular filtration rate. 37 Proteinuria, a characteristic of all dogs in our study, also is considered to be a clinical sign of target organ damage resulting from the effects of increased SBP on the kidney. 38 In a study of 45 dogs, those with a UPC ≥1 were found to have a mean SBP of 164 ± 23 mm Hg, which was significantly higher than those with UPC < 1.0 (139 ± 18 mm Hg).…”
Section: T a B L Ementioning
confidence: 92%